Risk management post financial crisis : a period of monetary easing - Batten, Jonathan; Wagner, Niklas F., 1969- (Contemporary studies in economic and financial analysis, 2014)
This volume provides further insights to post-crisis developments in the global economic and financial environment. It includes papers from leading authors from central banks, world-renowned universities and international organizations. Topics and issues addressed include: an overview of advances in risk management in the post financial crisis environment; the impact that complexity present in financial returns now plays in measuring reporting and risk; the role that sentiment and herding plays in distorting prices in financial markets; the procyclical impact of Basel III including effects on capital requirements and bank balance sheets; central bank monetary policies and bank liquidity in a world without quantitative easing; credit risk assessment and bank lending; and changes in the structure of international financial markets, including the rise and impact of financial markets in China and those financial products denominated in RMB. --